Análisis de la serie secular de precipitación anual del Observatorio Fabra (Barcelona) (1914-2020) - Martín Vide, Javier; Moreno-García, M.ª Carmen (Geographicalia, 2021)
The secular series of annual precipitation from the Fabra observatory in Barcelona (1914-2020) has been statistically analyzed, as well as those from four sub-periods (1914-1930, 1931-1960, 1961-1990, 1991-2020). The complete series does not present a statistically significant trend, and the values of the statistical parameters of the three 30-year sub-periods are similar. The 2-parameter Log-normal and Log-gamma probability distributions, with positive bias, offer a good fit for both the complete series and those of the 30-year series, with several others that also do so in each case. The Normal distribution, even though it is acceptable according to some of the fit tests, is ruled out due to its symmetry and its unlimited domain.